Dental developmental anomalies and post-eruption dental disorder - Raísa Sales de Sá; Lais Inês Silva Cardoso; Jordana Almeida Brito; Alina Nunes Braga; Laise Nascimento Correia Lima; Melaine Mont'Alverne Lawall-Silva; Erika Martins Pereira (Universidade Estadual de Campinas, 2021)
Panoramic radiographs are complementary exams to evaluate oral alterations in an early manner, these changes can be dental developmental anomalies, and post-eruption dental disorder. Aim: This study evaluated the findings in panoramic radiographs and correlated the variables of gender and dental location. Methods: A retrospective study was through the observation of 1.111 panoramic radiographs from the Radiology Department in Brazil. It was included patients from 5 to 79 years of age of both gender, and it classified the anomalies in shape, size, and number and post-eruption dental changes in and correlated with gender and location. Patients with syndromes were excluded from the sample. Results: The majority of the sample was composed of fameles 752 (67.7%), as to the frequency of dental developmental anomalies related lesions 684 cases (61.6%) and post-eruption dental disorder 567 (51.8%), in the radiographs. The most prevalent change was endodontic treatment (32.6%), followed by root dilaceration (25.9%), and included tooth (19.5%). The most prevailing alteration when correlated with the gender variables was the cyst root (p<0.01) in females, and orthodontic treatment (p=0.02) in males and the variable location in the mandible was root dilaceration, giroversion, impacted tooth, taurodontia, microdontia, and endodontic treatment (p<0.01). Conclusion: Our findings provide evidence that dental developmental anomalies e post-eruption dental disorder are frequent alterations in the population with particular characteristics of distribution by sex and location.